Synergistic structural and functional alterations in the medial prefrontal cortex of patients with high-grade gliomas infiltrating the thalamus and the basal ganglia - Yan, Zheng; Tang, Jun; Ge, Honglin; Liu, Dongming; Liu, Yong; Liu, Hongyi; Zou, Yuanjie; Hu, Xinhua; Yang, Kun; Chen, Jiu (Frontiers in Neuroscience, 2023)
Background: High-grade gliomas (HGGs) are characterized by a high degree of tissue invasion and uncontrolled cell proliferation, inevitably damaging the thalamus and basal ganglia. Thalamus exhibited a high level of structural and functional connectivity with default mode network (DMN). The present study investigates the structural and functional compensation within the DMN in HGGs invading the thalamus along with basal ganglia (HITBG). Methods: Thirty-three patients with HITBG and 22 healthy controls were enrolled, indicating demography and neurocognition (digit span test, DST). Among patients, 18 cases involved only in the left side while 15 cases involved in the right side. Moreover, the amplitude of low-frequency fluctuation (ALFF), regional homogeneity (ReHo), gray matter (GM) volume, and functional connectivity (FC) within the DMN among the subjects was assessed and compared with patients having left and right HITBG and healthy controls (HCs). Result: The medial prefrontal cortex (mPFC) region existed in synchrony between the significant increase of ALFF and GM volume in patients having left and right HITBG compared with HCs. In addition, elevated ReHo and GM precuneus volumes were displayed and overlapped only in patients having left HITBG. Patients with left and right HITBG had decreased GM volume in the contralateral hippocampus without functional variation. However, no significant difference in FC value was observed in the regions within DMN. DST scores were significantly reduced in HITBG without any significant correlation with functional and GM volume measurement. Conclusion: The synchrony pattern between structure and function existed in the neuroplasticity within the mPFC and precuneus. However, HITBG may have an inadequate capability of affecting the association of the regions within DMN. Furthermore, the contralateral hippocampus in HITBG exhibited atrophy. Thus, avoiding injury to these regions could delay the progress of neurological function damage in HGG.